From the Hunter to the Wolf, from the Wolf to the "Object": Managing in an analogical way the boundaries’ porosity between the man’s body, the wolf’s body and an artefact in West Mongolia - Charlier, Bernard (Swiss Journal of Sociocultural Anthropology, 2015)
This article aims at studying the relationships Mongolian herders who practice hunting entertain with a particular material object, that is a wolf’s ankle bone. I try to show through an ethnographic analysis of the cosmological status of the wolf and the hunting activity that the use of the wolf’s ankle bone by men accounts for an analogical perception of the human and non-human bodies, as well as objects.